Relationships between early maladaptive schemas, psychological distress, and coping strategies in people with diabetes - Golnezhad Monfared, Fatemeh; Meschi, Farahnaz; Mansoubi Far, Mohsen; Ataeifar, Robabeh; Sodagar, Sheida (Social Determinants of Health, 2024)
Background: Regarding the effect of early maladaptive schemas (EMSs) on the psychological distress (PD) of diabetic patients, various factors can play a mediating role. This study was to examine the associations between EMSs, PD, and coping strategies in people with diabetes. Methods: This descriptive correlational study was carried out on people with type 2 diabetes (T2D) referred to the diabetes clinic of Shariati Hospital in Tehran, in 2021. Here, 200 patients were included in the research and the selection method of people was convenient. Research tools included Kessler’s Psychological Distress Scale, Young Schema Questionnaire (YSQ-SF) and Coping Strategies Inventory (CSI). Data analysis was performed by SPSS 25 software and Smart-PLS 3, and structural equation method (SEM). Results: The findings revealed that EMSs have a significant and direct association with PD. Coping strategies had a mediating role in relation to EMSs and PD in people with T2D. As a result, 37% of PD was explained by EMSs and coping strategies. Conclusion: According to the results, in order to reduce the level of PD in people with T2D should be use of techniques aimed at enhancing EMSs and coping strategies.